Propagación (in situ) vegetativa del banano orito (Musa acuminata AA) con la utilización de la bencilaminopurina (6-BAP) en el cantón Valencia - Álvarez Galarza, Ricardo Orlando. (2019)
Vegetative propagation (in situ) of orito banana (Musa acuminata AA) was evaluated with the application of benzylaminopurine (6-BAP) in the canton of Valencia. In this study, a completely randomized design was used with four treatments (0 mg/L, 20 mg/L, 40 mg/L, 60 mg/L) four repetitions and five experimental units in order to evaluate the following variables; diameter, height, number of outbreaks and survival of corms, in addition to analyzing the benefit-cost ratio in each of the treatments. in this sense, the treatment that obtained the greatest number of diameter in the outbreaks was the treatment three who obtained averages of 3.23 cm, in the same way when evaluating the variable length of the corms who obtained the best averages was the treatment three with the application of 60 mg / L of benzylaminopurine when demonstrating lengths of 51.61 cm, with respect to the study of the number of outbreaks per corm, the treatment that stood out in this evaluation was treatment three, where averages of 2.32 shoots per corm were obtained. In this way it was possible to determine that in the variable survival of corms no statistical difference was found according to the tukey test (p ≥ 0.05), regarding the economic analysis the treatment without the application of the hormone benzylaminopurine proved to be the most moderate despite of this is not the most profitable because I present a lesser number of desirable characteristics unlike treatment three who obtained the best productive parameters and a cost benefit ratio of 1.90 that is to say that for every dollar of investment 0.90 ctvo is obtained. of profit dollar.